Effects of Cholesterol Extraction Process and Fat and Whey Protein Additions on Ice Cream Mixes. Issue 5 (23rd April 2019) - Hidalgo, María Eugenia; Bordino, Juliana; Acciarri, Giuliana; Fernández, Juan Manuel; Rozycki, Sergio; Risso, Patricia Hilda
Abstract: The aim of this work was to evaluate the cholesterol extraction process in ice cream mixes (ICMs) by using β‐cyclodextrin (βCD) and to analyze the effect of this extraction on the ICM rheological, stability, and sensory characteristics. The effects of fat and whey protein (WP) additions on ICM stability were also evaluated. The maximum percentage obtained for cholesterol extraction was 93.6%. The flow curves indicated that ICM showed a thixotropic behavior before and after cholesterol extraction, which was enhanced when the fat content and/or percentage of βCD increased. The stability of ICM with cholesterol‐reduced content (RCho‐ICM) was influenced by the fat content and/or the presence of WP. The RCho‐ICM with the highest fat and/or WP addition showed less tendency to melt and had the smallest amount of accumulated molten liquid. These latter ICMs presented the slowest melting rates. Also, RCho‐ICMs proved to be more stable than ICMs. RCho‐ICM samples obtained with a ratio of βCD/fat content of 1% w/w were evaluated by a trained sensory panel. In addition, an acceptability test of the sample with better sensory attributes was conducted. Practical Application: The effects of a cholesterol extraction process and fat and whey protein additions on the rheological and stability characteristics of ice cream mixes were evaluated. The extraction of cholesterol from an ice cream mix is interesting from a nutritional point of view and the extraction process of cholesterol itself may also help to improve the mix stability by controlling the fat and/or whey protein contents. These findings may prove useful as a starting point for the rational design of new functional ice cream mixes.